(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2011)
Petroleum ether extract of seeds of Psoralea corylifolia was recorded a maximum antifungal activity in Aspergillus flavus oryzae (93.5%) and A. tamarii (92.43%); Benzene extract recorded a maximum inhibition in A. niger (88.10%), A. flavus oryzae (83.80%) and A. tamarii (81.10%). In chloroform extract A. tamarii recorded 74.60% and A. niger showed 74.16% inhibition. In methanol extract A. tamarii and A. flavus oryzae recorded 69.50% and in ethanol extract A. flavus oryzae showed 74.63% and A. flavus recorded 67.10% inhibition in 2.0% concentration of extract. Compared to synthetic fungicides Captan and Thiram, Captan recorded 85.0% to 95.0% inhibition and Thiram showed 100% inhibition against all the test fungi. Among the three different fractions I, II and III, Fraction II showed a significant activity against all test fungi compared to fraction I and fraction III.